Observation of the Rotational Doppler Effect With Structured Beams in Atomic Vapor - Qiu, Shuwei; Wang, Jinwen; Yang, Xin; Cao, Mingtao; Zhang, Shougang; Gao, Hong; Li, Fuli (Frontiers in Physics, 2022)
A vector beam with the spatial variation of polarization states has attracted keen interest and is progressively applied in quantum information, quantum communication, precision measurement and so on. In this letter, the spectrum observation of the rotational Doppler effect based on the coherent interaction between atoms and structured light in an atomic vapor is realized. The geometric phase and polarization of the structured beam are generated and manipulated by using a flexible and efficacious combination system, converting an initial linearly polarized Gaussian beam into a phase vortex beam or an asymmetric or symmetric vector beam. These three representative types of structured beam independently interact with atoms under a longitudinal magnetic field to explore the rotational Doppler shift associated with the topological charge. We find that the rotational Doppler broadening increases obviously with the topological charge of the asymmetric and symmetric vector beam. There is no rotational Doppler broadening observed from the spectrum of the phase vortex beam, although the topological charge and spatial profile of the beam change. This study can be applied to estimate the rotational velocity of the atom-level or molecule-level objects, measure the intensity of magnetic fields and study the quantum coherence in atomic ensembles.